(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores widely spread pathologies of the cervical mucosa in gynecology, specifically focusing on the types of true erosion and pseudo erosion, their diagnostic criteria, and pathogenetic differences. The study analyzes the impact of hormonal status—including the consequences of uncontrolled or incorrect medication intake—infectious-viral factors, and postpartum complications such as ectropion. The risk of the disease progressing to chronic bleeding and cervical malignancies (cancer) is evaluated, and modern therapeutic approaches are substantiated.